The Principle of Fair Value in Accounting: Methodological Design and Use Problems - Alexander SUKHAREV; Yulia SCHMIDT; Irina ZHUPLEY; Evgeniia ZADVORNEVA; Oksana IVANOVA (Communications of International Proceedings, 2021)
The article presents an analysis of the methodological aspects of using the fair value principle to assess assets and liabilities, in comparison with the historical cost approach. The idea of the need for a transition in a digital society to a multi-value valuation of assets and liabilities in accounting and financial reporting is expressed, which will provide more information about the financial and economic condition of the organization.
Keywords: Value; Multi-Value Valuation; Precautionary Principle; RAS.